(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
A study was conducted to investigate the stress coping styles among post graduate teachers. This study included the categorical variables gender, location, type of school management, nature of the school, marital status and educational qualification. Stress coping styles scale was standardized by Ying Ming Lin (2010). It contains 28 items. Suitable objectives were framed and set the hypotheses to test the objectives. Normative survey method was adopted in this study. In the study 260 post graduate teachers from 13 selected schools formed the sample. They were from government, government aided and private school. The collected data was statically analysed by using percentage analysis and differential analysis. The finding of this study reveals that the level of stress coping styles of post graduate teachers is moderate and there is no significant difference between the post graduate teachers stress coping styles on their type of school management.